Control problems and devices in manufacturing technology 1980 : proceedings of the 3rd IFAC/IFIP Symposium, Budapest, Hungary, 22-25 October 1980 (Manufacont '80) - Ellis, T. M. R., 1942- (Published for the International Federation of Automatic Control by Pergamon Press, 1981)
Control Problems and Devices in Manufacturing Technology 1980 presents the proceedings of the 3rd IFAC/IFIP Symposium on Control Problems and Devices in Manufacturing Technology, held in Budapest, Hungary, on October 22-25, 1980. This book discusses the increasing use of robots in both machining and assembly.